Jelly surge in the Mediterranean Sea: threat or opportunity? - GRAVILI, CINZIA (Mediterranean Marine Science, 2020)
The rise in water temperature in the Mediterranean Sea, and associated migrations of temperate marine biota, are occurring in the context of a global warming causing an expansion of the tropical jellyfish range, exacerbating jellyfish outbreaks linked to coastal development, nutrient loading, and overfishing. The gelatinous component of plankton is considered as ‘the dark side of ecology’ capable of appearing and disappearing at unpredictable times. In the last decade an increasingly high number of gelatinous plankton blooms are occurring and this makes us wonder if ‘a Mediterranean Sea full of jellyfish is a probable future’. The reasons for rising jellyfish blooms are, probably, manifold. Current studies are aimed to highlight how climatic change is interacting with the Mediterranean ecosystem favouring entrance, abundances and success of alien species and triggering ‘regime shifts’ such as from fish to jellyfish. Jellyfish damage the economic success of power plants, fish farms, tourism, and affect fisheries consuming larvae of commercial fish species. On the other hand, several studies were also taken into account on uses for jellyfish as biofuels and foods but more experimentation is needed to improve the first encouraging results.